KOMPARASI PERANG UHUD DAN MUT'AH DALAM NASKAH PENDIDIKAN ISLAM KARYA NASRUDIN TAHA - Fadhilah, Annisa; Gifari, Afif Rahim; Fath, Muhammad Naufal Ashrof; Hudaidah; Yati, Risa Marta (Khazanah: Jurnal Sejarah dan Kebudayaan Islam, 2025)
The present study aims to compare the Battle of Uhud and the Battle of Mu’ta as described in Nasrudin Taha’s work on Islamic Education. The problem examined in this study concerns the importance of understanding the differences in characteristics, strategies, as well as the moral and spiritual lessons of these two historical events within the context of teaching Islamic history. A comparative study is needed because both battles reflect different situations and dynamics, yet each contains important educational values for shaping the character of Muslim learners. The purpose of this research is to identify the similarities and differences between the Battle of Uhud and the Battle of Mu’ta, and to explore the relevance of their historical values in Islamic education. This study employs library research with a qualitative–descriptive approach, in which data are analyzed from Nasrudin Taha’s text along with other supporting sources. The findings show that the Battle of Uhud emphasizes lessons on obedience and the consequences of internal strategic negligence, whereas the Battle of Mu’ta highlights steadfastness and courage in facing an enemy of significantly greater strength. Both battles contribute meaningfully to the development of leadership, faith, and discipline within Islamic education.